Neuronal‐like differentiated SH‐SY5Y cells adaptation to a mild and transient H2O2‐induced oxidative stress. (12th February 2018) - Akki, Rachid; Siracusa, Rosalba; Morabito, Rossana; Remigante, Alessia; Campolo, Michela; Errami, Mohammed; La Spada, Giuseppina; Cuzzocrea, Salvatore; Marino, Angela
Abstract : Preconditioning (PC) is a cell adaptive response to oxidative stress and, with regard to neurons, can be considered as a neuroprotective strategy. The aim of the present study was to verify how neuronal‐like differentiated SH‐SY5Y cells adapt to a mild and transient H2 O2 ‐induced oxidative stress and, hence, whether may be considered as more sensitive cell model to study PC pathways. A first screening allowed to define H2 O2 concentrations for PC (10μM‐50μM), applied before damage(100μM H2 O2 ). Cell viability measured 24 hours after 100μM H2 O2 –induced damage was ameliorated by 24‐hour pre‐exposure to low‐concentration H2 O2 (10μM‐30μM) with cell size as well restored. Markers for apoptosis (Bcl‐2 and Bad), inflammation (iNOS), and redox system (MnSOD) were also determined, showing that, in cells pre‐exposed to 10μM H2 O2 and then submitted to 100μM H2 O2, Bcl‐2 levels were higher, Bad and iNOS levels were lower than those observed in damaged cells, and MnSOD levels were unchanged. Such findings show that (1) neuronal‐like differentiated SH‐SY5Y cells are a suitable model to investigate PC response and more sensitive to the effect of a mild and transient H2 O2 ‐induced oxidative stress with respect to other neuronal cells; (2) 10μM H2 O2 –induced PC is mediated by apoptotic and inflammatory pathways, unlike antioxidant system; (3) such neuroprotective strategy and underlying signals proven in neuronal‐like differentiated SH‐SY5Y cells may contribute to understand in vivo PC mechanisms and to define a window for pharmacological intervention, namely, related to ischemic brain damage. Significance of the study: Neuronal‐like differentiated SH‐SY5Y cells are a suitable model to investigate PC, an endogenous neuroprotective response to a mild and transient H2 O2 ‐induced oxidative stress, elicited by 24‐hour exposure to very low H2 O2 concentrations and mediated by both apoptotic and inflammatory pathways. This model reflects in vivo PC mechanisms occurring after brain trauma and provides novel information about pathways and time of protection useful for an appropriate pharmacological intervention.